2016
DOI: 10.1016/j.antiviral.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of enterovirus D68, enterovirus 71, and rhinovirus 87 strains to various antiviral compounds

Abstract: Compounds were evaluated for antiviral activity in rhabdomyosarcoma (RD) cells against a recent 2014 clinical isolate of enterovirus D68 (EV-D68), a 1962 strain of EV-68D, rhinovirus 87 (RV-87, serologically the same as EV-D68), and enterovirus 71 (EV-71). Test substances included known-active antipicornavirus agents (enviroxime, guanidine HCl, pirodavir, pleconaril, and rupintrivir), nucleobase/nucleoside analogs (3-deazaguanine and ribavirin), and three novel epidithiodiketopiperazines (KCN-2,2’-epi-19, KCN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 40 publications
2
57
0
2
Order By: Relevance
“…The study demonstrated that the compound had effective antiviral activity against the five serotypes (median EC50 of 0.02 μg/ml) and against the majority of the untyped clinical isolates. Two separate studies also demonstrated findings in accord with this, showing antiviral activity of pleconaril against RV-14 and RV-87 [ 33 , 34 ]. Interestingly, analysis of several RV serotypes has also assessed structural features of amino acids that make up the VP1 protein, and has identified several common sequences and mutations that confer natural resistance to capsid binding compounds such as pleconaril, as well as those that could arise as a result of antiviral drug treatment [ 39 , 40 ].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The study demonstrated that the compound had effective antiviral activity against the five serotypes (median EC50 of 0.02 μg/ml) and against the majority of the untyped clinical isolates. Two separate studies also demonstrated findings in accord with this, showing antiviral activity of pleconaril against RV-14 and RV-87 [ 33 , 34 ]. Interestingly, analysis of several RV serotypes has also assessed structural features of amino acids that make up the VP1 protein, and has identified several common sequences and mutations that confer natural resistance to capsid binding compounds such as pleconaril, as well as those that could arise as a result of antiviral drug treatment [ 39 , 40 ].…”
Section: Introductionsupporting
confidence: 60%
“…In the context of RV infection, ribavirin and a number of modified analogs have been shown to have moderate antiviral activity against RV-13 [ 32 ]. RV-87 was also reported to be moderately susceptible to treatment, although other in vitro studies using alternative serotypes of RV, such as RV-14, have suggested that ribavirin is relatively ineffective [ 33 , 34 ]. However, clinical reports of ribavirin therapy twinned with the use of IFNα-2a have indicated that combinatorial therapy could be of value with patients reportedly exhibiting enhanced clearance of RV infections following treatment with these two compounds [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral compounds selected for the study include 6-azauridine (Flint et al, 2014; Rada and Dragun, 1977; Smee et al, 1987), BCX4430 (Julander et al, 2014; Taylor et al, 2016), 3-deazaguanine (Allen et al, 1977; Smee et al, 2016), EICAR (De Clercq, 2015; De Clercq et al, 1991), favipiravir (Furuta et al, 2013; Mendenhall et al, 2011), Infergen™ (interferon alfacon 1, hereafter referred to as infergen) (Julander et al, 2007; Morrey et al, 2004), mycophenolic acid (Cline et al, 1969; Takhampunya et al, 2006; To et al, 2016), ribavirin (Sidwell et al, 1972; Smee et al, 1987; Westover et al, 2016), and tiazofurin (Baker et al, 2003; Huggins et al, 1984). All of the compounds have antiviral properties, but against different viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 7 ] recorded many compounds isolated from biogenic sources with anti-EV71 activity over the period between 2005–2015. Recently reported anti-EV agents include aminopyridyl 1,2,5-thiadiazolidine 1,1-dioxides [ 8 ], 3-aryl-1,2,4-oxadiazoles [ 7 ], benzothiophenes [ 9 ], N 6 -benzyladenosine [ 10 ], 3-benzyl-1,3-benz-oxazine-2,4-diones [ 11 ], biaryl-substituted quinolones [ 12 ], diarylhydrazides [ 13 ], disaccharide heparan sulfates [ 5 ], epidithiodiketopiperazines [ 14 ], isopentenyladenosine [ 15 ], α-keto amides [ 16 , 17 ], nitrobenzonitriles [ 18 ], peptidomimetic aldehydes [ 19 ], quinoline–thiophene conjugates [ 20 ], sophoridine alkaloid [ 21 ], stilbenoids [ 22 ], multi-tryptophan derivatives [ 23 ], and others.…”
Section: Introductionmentioning
confidence: 99%